Molar mass distribution by size exclusion chromatography: Comparison of multi-angle light scattering and universal calibration - Podzimek, Štěpán (Wiley-Blackwell, 2019)
Series of polymers of various molar mass, chemical composition, and molecular architecture was analyzed by size exclusion chromatography (SEC) coupled with a multi-angle light scattering (MALS) photometer and an online viscometer. The molar mass averages were determined from the signal of MALS or calculated from the intrinsic viscosity and universal calibration. The comparison of the obtained results showed significant differences between the two methods. The MALS detection was shown to be more accurate for the determination of the weight-average molar mass and less vulnerable to the spreading of polymer peak by band broadening. The universal calibration can yield more accurate estimation of the number-average molar mass of branched polymers. It is also significantly more accurate for the characterization of fluorescent polymers than MALS with a regular laser of 660 nm. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47561.
Distribuce molární hmotnosti metodou gelové permeační chromatografie: Porovnání víceúhlového rozptylu světla a universální kalibrace
Keywords: light scattering; molar mass; properties and characterization; separation techniques; size exclusion chromatography; universal calibration; rozptyl světla; molární hmotnost; vlastnosti a charakterizace; separační techniky; gelová permeační chromatografie; universální kalibrace